2013
DOI: 10.1016/j.aap.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and occupational injuries in U.S. underground coal mines

Abstract: Background-Coal plays a crucial role in the U.S. economy yet underground coal mining continues to be one of the most dangerous occupations in the country. In addition, there are large variations in both profitability and the incidence of occupational injuries across mines.Objective-The objective of this study was to examine the association between profitability and the incidence rate of occupational injuries in U.S. underground coal mines between 1992 and 2008.Data and method-We used mine-specific data on annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 30 publications
(27 reference statements)
4
30
1
Order By: Relevance
“…Our theory is not only consistent with anecdotal evidence from the motor carrier industry as detailed by Adams (), Belzer (), and Ouellet (), it is also consistent with findings from other industries such as coal mining (Asfaw et al. ). For example, Wu and Pagell () find that even at companies considered exemplars on social and environmental sustainability, the fear of falling short on financial performance metrics results in managers making short‐term decisions designed to improve financial to the detriment of social and environmental performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our theory is not only consistent with anecdotal evidence from the motor carrier industry as detailed by Adams (), Belzer (), and Ouellet (), it is also consistent with findings from other industries such as coal mining (Asfaw et al. ). For example, Wu and Pagell () find that even at companies considered exemplars on social and environmental sustainability, the fear of falling short on financial performance metrics results in managers making short‐term decisions designed to improve financial to the detriment of social and environmental performance.…”
Section: Discussionsupporting
confidence: 92%
“…As explained by Asfaw et al. () and Madsen (), safety investments fall within this category of decisions, and thus managers must be cognizant not to let safety performance entropy. Moreover, in light of carrier selection decisions being driven primarily by reliability versus cost (Murphy et al.…”
Section: Discussionmentioning
confidence: 99%
“…We argue the evidence favors the prediction that owner–operators receive greater benefits from unsafe operation because economic strains result in myopic decisions that favor actions that alleviate those strains at the cost of safety (Vaughan ; Asfaw et al. ). Third, we draw on theory regarding how classes of safety behaviors differ regarding how their violation can alleviate financial strain (Miller and Saldanha ) to develop the most precise predictions to date for how carriers’ owner—operator use affects carrier‐level safety.…”
Section: Background Literaturementioning
confidence: 82%
“…This fact then has seen many companies (coal industry inclusive) ignoring environmental and safety investments in their operations as they are considered additional costs aimed at reducing profits. However, much as heavy investment into safer and cleaner environment (which are dubbed ''undesirable outputs'') is considered not necessary for profits sake, studies have shown that when safety measures have been compromised and accidents have occurred, more loses are realized due to workers' compensation payment and production disruptions due to injuries and/or deaths (Moore et al 2010;Yakovlev and Sobel 2010;Asfaw et al 2013). Likewise, deterioration of the environment can be costly to the production process itself and the local environment (Si et al 2010).…”
Section: Introductionmentioning
confidence: 98%